ANALISA POTENSI KEBAKARAN DAN LEDAKAN PADA TANGKI LNG ISO TANK 40 Ft DI PT X TAHUN 2022 - Juni Trihardiyanto; Fatma Lestari (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
LNG (Liquified Natural Gas) has a high risk of fire and explosion. The increasing domestic demand for LNG has forced several new alternatives in the process of delivering LNG to consumers throughout Indonesia. LNG transportation in Indonesia is slowly starting to shift from large scale to small scale with the alternative of using ISO Tanks, so that it can reach locations that do not have special LNG port facilities. PT. X is one of the LNG refineries in Indonesia which currently serves LNG shipments by cargo or ISO Tanks. The threat of fire and explosion at oil and gas facilities cannot be avoided, so an accurate assessment is needed so that the risk mitigation can be carried out appropriately. With high standardization of work safety and security processes, preventive efforts in the LNG filling and filling process must be ensured in a safe condition. This paper aims to assess the potential for fire and explosion in a 40 ft LNG ISO Tank that performs filling and temporary storage at facilities owned by PT. X. Analysis of the potential for fire and explosion in the LNG ISO Tank was carried out using the Dow's Fire and Explosion Index 7th Edition method. The results of the analysis obtained that the F&EI value at the facilities at PT. X was 139.48 so that it was included in the category of severe hazard level. This category is the reference for proper heating to reduce the risk of fire and explosion